1MDB the scandal that brought down a government : a prime minister, a whizz kid and the biggest kleptocracy the world has ever known - Gunasegaram, P. (Strategic Information and Research Development Centre, 2018)
This book is a gripping account of the biggest, most audacious kleptocracy the world has ever known - over RM40 billion lost or stolen by a corrupt Malaysian government through 1Malaysia Development Berhad or 1MDB. It has all the elements of a Hollywood thriller with a cast featuring a sultan, a prime minister, his high-flying and even more high-spending wife, and a baby-faced whizz kid as the mastermind who was in his late twenties when it all started and who cavorted with actors and socialites such as Leonardo DiCaprio and Paris Hilton on yachts and other expensive places.